Assessment of the Invasive Alien Plant Species Lantana camara in Nile River Millennium Park, Bahir Dar, Ethiopia (Global Journal of Science Frontier Research, 2017)
Lantana camara is the major invasive alien species in Nile River Millennium Park and it is introduced for ornamental purpose to the park intentionally. It reproduces by seed, root and vegetative multiplication, and disseminated by animals particularly birds and human intentional gardening are the major spreading mechanisms. Local communities are highly frustrated by the negative impacts of Lantana camara which includes competing animal feed, biodiversity loss, closing roads, and hiding harmful wild animals like rodents, snakes, mongoose, etc. According to the present study Lantana camara rate and scale of invasion has been increasing at an alarming rate affecting socio-economic status of the community and adverse effect to the biodiversity at large since its introduction. This is because Lantana spreading mechanisms are in multiple ways such as local human activity, by animals particularly birds, wind and its prolific seed production and easy dispersal, and multiplication nature. This, therefore, needs for an integrated, coordinated and multi-stakeholder and multiple level actions that the community, government and development partners shall participate in the eradication of the invasive plant Lantana camara.
Keywords: assessment; invasive alien species; lantana camara; nile river millennium park